Autolysis of Lactococcus lactis caused by induced overproduction of its major autolysin, AcmA. - Buist, G (1997)
The optical density of a culture of lactococcus lactis MG1363 was reduced more than 60% during prolonged stationary phase. Reduction in optical density (autolysis) was almost absent in a culture of an isogenic mutant containing a deletion in the major autolysin gene, acmA. An acmA mutant carrying multiple coples of a plasmid encoding AcmA lysed to a greater extent than the wild-type strain did. Intercellular action of AcmA was shown by mixing end-exponential-phase cultures of an acmA deletion mutant and a tripeptidase (pepT) deletion mutant. PepT, produced by the acmA mutant, was detected in the supernatant of the mixed culture, but no PepT was present in the culture supernatant of the acmA mutant. A plasmid was constructed in which acmA, lacking its own promoter, was placed downstream of the inducible promoter/operator region of the temperate lactococcal bacteriophage r1t. After mitomycin induction of an exponential-phase culture of L. lactis LL302 carrying this plasmid, the cells became subject to autolysis, resulting in the release of intracellular proteins.